Epidemiology of prelingual sensorineural hearing impairment at a children's center in Bogotá, Colombia between 1997 and 2008 (2011)
Introduction: Hearing loss is a frequent problem in childhood with an incidence of about one case per 1000 births. Control of deafness should be aimed at prevention and early diagnosis in efforts to provide appropriate treatment and stimulate adequate communication in children affected. The objective of this study was to determine the prevalence of different etiologies among deaf children with a diagnosis of prelingual sensorineural hearing loss referred to the Fundacion CINDA in Bogota, Colombia, between 1997 and 2008.Materials and methods: The medical records were selected from those with prelingual hearing loss. Information was gathered in a format containing variables related to the risk factors suggested by the Joint Committee of Infant Hearing.Results: We studied 254 children; boys and girls were equally distributed. The most common etiological diagnosis was "unknown cause" , followed by genetic causes (31 cases), and 38 cases from TORCH infections (toxoplasmosis, others syphilis, rubella, cytomegalovirus, herpes), with rubella as the most common cause.Conclusions: Review of prenatal, perinatal, and postnatal history often reveals the cause of the deafness in children; therefore, appropriate evaluation of pregnant mothers could result in decreased frequency of deafness in children in our country.